Economic interdependence between Japan and rest of Asia. - Sion, Hui Chin. (2008)
This papaer investigates the extent of economic interdependence between Japan and rest of Asia. From our cointegration analysis using the 2-step Engle-Granger Approach, we find no support for the notion that Japan is the engine of economic growth in the Asian region.